Metode Keteladanan dan Etika Mulia dalam Model Pembelajaran STAD (Student Team Achievement Divisions) Sebagai Suatu Pola Interaksi Edukatif pada Pembelajaran Akuntansi dan Matematika - Rosita, Rosita; Haryanto, Tri; Sulistorini, Eni Jufriyah (STIE Surakarta, 2012)
Education is a power and deliberate effort to create an atmosphere of studying in the learning process, so that learners are active developing their potential. Modeling method and ethics is a very important method and factual is ever happen by the Prophet Muhammad during in the process of education and learning. The history of education had proven that the Prophet Muhammad is a figure of educator and learner who succeed in forming an educated generation and strong personality through modeling method and ethic noble morality.Â Â Â Â Â Â Â Â Â Â Â When further, based on the results of previous studies on model of excellence STAD and indisputable historical facts about the success of Prophet Muhammad SAW builds humanâs characterâs into a generation educated and ethic noble morality, modeling method and ethics are reflected in the model STAD and learning are inextricably linked to cultivate studentsâ personality that ethic noble. In the process of development in the world of education, it is urgent if fostered noble ideals and ethics within which learners can be integrated in the learning model employed by teachers and lecturer.Â Â Â Â Â Â Â Â Â Â Â Modeling idealsand ethics that need to be developed and nurtured in the learning process through STAD models so that learners used to develop a positive attitude to form the personality of an independent, strong, caring and moral in turn achieved success and the learnerâs successful achieve performance. In the last of the formation of character education as a result of the modeling ideals and ethics in learnersâ selves.